Preparation method of lidocaine long-time slow-release prefilled needle
By using materials such as carboxymethylcellulose, hydroxypropylcellulose and sodium hyaluronate to form a sustained release system, controlling the release of lidocaine, solving the problem of short pain relief time in the prior art, and achieving long-term stability pain relief and high stability.
Patent Information
- Application Number
- CN202411333843.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The existing lidocaine can relieve cosmetic pain injected for a short time and cannot meet the clinical needs of patients for long-term pain relief.
Using low viscosity and medium viscosity sodium carboxymethylcellulose, hydroxypropylcellulose and sodium hyaluronate, the salt complex of acid sodium carboxymethylcellulose and lidocaine is formed, and the polycaine is combined with polycaine. Ester microspheres and polymethyl methacrylate microspheres form a sustained release system, controlling the release rate of lidocaine and prolonging the pain relief time.
It has achieved a long-term pain relief effect, good stability and strong salt tolerance, avoided the side effects caused by the rapid release of the drug, and met the clinical needs of the pain relief duration.
Smart Images

Figure BDA0005057733230000121 
Figure BDA0005057733230000131
Abstract
Description
Technical Field
[0001] A method for preparing a lidocaine sustained-release prefilled needle. Specifically, the invention relates to a method for preparing a lidocaine sustained-release prefilled needle capable of long-term sustained release and long-term analgesia. Technical Background
[0002] Injectable beauty is a cosmetic procedure that improves facial contours, fills facial depressions and fine lines by injecting specific fillers. This technique uses a fine needle to inject specific ingredients into specific areas to achieve the purpose of lifting contours, increasing volume and improving wrinkles. Injectable beauty can achieve a more natural effect, and the fillers can be customized according to individual facial features and needs.
[0003] In order to relieve pain after injection, lidocaine local anesthetic is added to the above-mentioned medical cosmetic fillers. Usually, the pain relief time of lidocaine directly injected is only tens of minutes, and the duration of the pain relief in the above-mentioned medical cosmetic fillers can last for several hours. However, the pain after injection can last for several days, which cannot meet clinical needs.
[0004] Therefore, in reality, it is necessary to prepare lidocaine preparations with longer-lasting analgesic effects, and the analgesic time should be consistent with clinical needs, neither too long nor too short. Summary of the invention
[0005] The present invention relates to a method for preparing a lidocaine long-term sustained-release (long-term analgesic) prefilled needle, the method comprising:
[0006] 1) Low viscosity sodium carboxymethyl cellulose Akucell AF 1505 (with a substitution degree of 0.7-1, a sodium content of about 8% wt / wt, a neutralization degree of 95-100%, and a viscosity of 40-70 mPa·s at a concentration of 1% wt / wt), medium viscosity sodium carboxymethyl cellulose Akucell AF 2085 (with a substitution degree of 0.7-1, a sodium content of about 8% wt / wt, a neutralization degree of 95-100%, and a viscosity of 200-400 mPa·s at a concentration of 1% wt / wt), medium viscosity hydroxypropyl cellulose Klucel JF (with a molecular weight of about 140,000 Daltons, and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt) or / and Klucel GF (whose molecular weight is about 370,000 Daltons and viscosity is 150-400 mPa·s at a concentration of 2% wt / wt) is dispersed in water, wherein the concentration of the low-viscosity sodium carboxymethyl cellulose is 1-5% wt / wt (based on the final total amount of 100%, that is, 1-5 parts per 100 parts by weight), and the concentration of the medium-viscosity sodium carboxymethyl cellulose is 1-5% wt / wt (based on the final total amount of 100%, that is, 1-5 parts per 100 parts by weight). The concentration of the hydroxypropyl cellulose is 2-6% wt / wt (based on the final total amount of 100%, that is, 2-6 parts per 100 weight parts), hydrochloric acid solution is added to convert the sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.1-0.5 times the (molar) amount of the total sodium in the sodium carboxymethyl cellulose, and the mixture is mixed. If necessary, small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200 Da to obtain a colloidal solution A;
[0007] 2) Adding the prototype lidocaine or its ethanol solution or its aqueous dispersion to the colloidal solution A, wherein the (molar) amount of lidocaine is 0.95-1 times the (molar) amount of hydrochloric acid in the above hydrochloric acid solution, and adding lidocaine hydrochloride, wherein the (molar) amount of lidocaine hydrochloride is 0.2-0.5 times the (molar) amount of hydrochloric acid in the above hydrochloric acid solution, mixing, and leaving at room temperature for 2-4 hours to obtain a colloidal solution B;
[0008] 3) Adding sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 1-5% wt / wt (based on the final total amount of 100%, i.e., 1-5 parts per 100 parts by weight) to obtain colloidal solution C;
[0009] 4) Add polycaprolactone microspheres and / or polymethyl methacrylate microspheres and / or polylactic acid copolymer and / or glycerol to the colloidal solution C, add water to the total amount, mix well, and obtain the product. DETAILED DESCRIPTION
[0010] The concentration of the low-viscosity sodium carboxymethyl cellulose is preferably 3-4% wt / wt.
[0011] The concentration of the medium-viscosity sodium carboxymethyl cellulose is preferably 2-3% wt / wt.
[0012] The concentration of the hydroxypropyl cellulose is preferably 3-4% wt / wt.
[0013] The usage ratio of the low-viscosity sodium carboxymethyl cellulose to the medium-viscosity sodium carboxymethyl cellulose is 1:0.5-1.5, preferably 1:0.8-1.2.
[0014] The present invention adopts the salt (or complex) formed by acid sodium carboxymethyl cellulose converted from moderately low-viscosity and medium-viscosity sodium carboxymethyl cellulose and prototype lidocaine as the main sustained-release material and the main sustained-release mechanism. The salt (or complex) formed by acid sodium carboxymethyl cellulose with moderately low viscosity and medium viscosity and prototype lidocaine can release lidocaine at two moderately different speeds, and can provide sustained-release effects at medium speed and low speed, thereby achieving analgesia for a longer period of time.
[0015] In the present invention, the salt (or complex) formed by acidic sodium carboxymethyl cellulose converted from sodium carboxymethyl cellulose of lower or higher viscosity and prototype lidocaine releases lidocaine too slowly (no or weak analgesic effect) or too quickly (short analgesic time or large side effects), which does not meet the requirements of the present invention.
[0016] The present invention acidifies part of the sodium carboxyl in sodium carboxymethyl cellulose and retains part of the sodium carboxyl without completely acidifying, which is beneficial to maintaining its relatively high hydrophilicity and preventing the aggregation and precipitation of the acidic carboxymethyl cellulose salt and the salt (or complex) formed with the prototype lidocaine, thereby not affecting the sustained release effect, not causing no or weak analgesic effect or short analgesic time, and failing to meet the requirements of the present invention.
[0017] The invention is simultaneously mixed with an appropriate amount of lidocaine hydrochloride to release the lidocaine at a conventional speed, thereby achieving a faster analgesic effect.
[0018] The present invention also uses medium-viscosity hydroxypropyl cellulose and relatively high molecular weight sodium hyaluronate as auxiliary sustained-release materials to enhance the sustained-release effect and prolong the sustained-release time, thereby further prolonging the analgesic time.
[0019] The functions of medium viscosity hydroxypropyl cellulose also include: 1) preventing the aggregation and precipitation of acid carboxymethyl cellulose sodium and its salt (or complex) formed with prototype lidocaine, especially in the presence of salt, especially in the state of high ionic strength;
[0020] 2) It can also prevent the aggregation and precipitation of high molecular weight sodium hyaluronate in the presence of salt, especially in high ionic strength conditions, especially in the presence of calcium salt and magnesium salt.
[0021] In the present invention, the hydroxypropyl cellulose with lower viscosity has poor blocking effect and is difficult to prevent aggregation and precipitation due to its low viscosity, and the above-mentioned effect cannot be achieved. The hydroxypropyl cellulose with higher viscosity has poor salt resistance and is difficult to prevent aggregation and precipitation due to its high viscosity, and the above-mentioned effect cannot be achieved. In addition, due to its high viscosity, the operation is difficult or the process becomes complicated, for example, the above-mentioned room temperature placement time (i.e., the time for the salt (or complex) formed by acid sodium carboxymethyl cellulose and prototype lidocaine) is too long.
[0022] Medium-viscosity hydroxypropyl cellulose cannot achieve the above-mentioned effects, which will affect the sustained-release effect, resulting in no or weak analgesic effect or short analgesic time, making it difficult to achieve long-term analgesia, and may even cause "dumping" of lidocaine hydrochloride, that is, a one-time rapid release, which may have serious consequences.
[0023] The advantages of the present invention over the prior art are:
[0024] 1) It can relieve pain quickly and for a longer period of time, and the pain relief time is consistent with clinical needs, neither too long nor too short;
[0025] 2) Good stability, resistance to salt and high ionic strength;
[0026] 3) Not “pouring out”;
[0027] 4) Lower incidence of side effects.
[0028] Example
[0029] The following non-optional example, i.e., the method for preparing a prefilled needle, further describes a preferred embodiment within the scope of the present invention. There are many variations of these embodiments within the scope of the present invention.
[0030] Example 1
[0031] 1) Disperse low-viscosity sodium carboxymethylcellulose Akucell AF 1505 (sodium content 8%), medium-viscosity sodium carboxymethylcellulose Akucell AF 2085 (sodium content 8%), and medium-viscosity hydroxypropylcellulose Klucel JF in water, wherein the concentration of Akucell AF 1505 is 2% wt / wt (based on the final total amount of 100%, that is, it contains 2 parts per 100 parts by weight), and the concentration of Akucell AF 2085 is 2% wt / wt (based on the final total amount of 100%, that is, it contains 2 parts per 100 parts by weight). The concentration of 2085 is 2% wt / wt (based on the final total amount of 100%, that is, it contains 2 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 4% wt / wt (based on the final total amount of 100%, that is, it contains 4 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.2 times the (molar) amount of total sodium in the above sodium carboxymethyl cellulose, the mixture is mixed, and small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200 Da to obtain a colloidal solution A;
[0032] 2) Adding an ethanol solution of prototype lidocaine to colloidal solution A, wherein the molar amount of lidocaine is 0.98-1 times the molar amount of the above hydrochloric acid, and adding lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.4 times the molar amount of the above hydrochloric acid, mix well, and place at room temperature for 2-4 hours to obtain colloidal solution B;
[0033] 3) Sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons is added to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight), to obtain colloidal solution C;
[0034] 4) Add 8% wt / wt (based on the final total amount of 100%, that is, 8 parts per 100 parts by weight) of polycaprolactone microspheres and 15% wt / wt (based on the final total amount of 100%, that is, 15 parts per 100 parts by weight) of glycerol to the colloidal solution C, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).
[0035] Comparative Example 1-1
[0036] The Akucell AF 1505 (viscosity of 40-70 mPa·s at a concentration of 1% wt / wt) in Example 1 was replaced with Akucell AF 2085 (viscosity of 200-400 mPa·s at a concentration of 1% wt / wt) (ie, all the sodium carboxymethyl cellulose was AF2085), and the others remained unchanged.
[0037] Comparative Example 1-2
[0038] The Akucell AF 1505 in Example 1 was replaced with Akucell AF 0305 (viscosity of 10-15 mPa·s at a concentration of 1% wt / wt), and the other parameters remained unchanged.
[0039] Comparative Examples 1-3
[0040] The Akucell AF 2085 in Example 1 was replaced with Akucell AF 1505 (i.e., the sodium carboxymethyl cellulose was all AF 1505), and the other contents remained unchanged.
[0041] Comparative Examples 1-4
[0042] The Akucell AF 2085 in Example 1 was replaced with Akucell AF 2405 (viscosity of 800-1200 mPa·s at a concentration of 1% wt / wt), and the other components remained unchanged.
[0043] Comparative Examples 1-5
[0044] The hydroxypropylcellulose Klucel JF in Example 1 (having a molecular weight of about 140,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt) was replaced with Klucel EF (having a molecular weight of about 80,000 Daltons and a viscosity of 200-600 mPa·s at a concentration of 10% wt / wt), and the other components remained unchanged.
[0045] Comparative Examples 1-6
[0046] The hydroxypropylcellulose Klucel JF in Example 1 was replaced with Klucel MF (whose molecular weight was about 850,000 Daltons and viscosity was 4000-6500 mPa·s at a concentration of 2% wt / wt), and the other contents remained unchanged.
[0047] Example 2
[0048] 1) Disperse low-viscosity sodium carboxymethylcellulose Akucell AF 1505 (sodium content 8%), medium-viscosity sodium carboxymethylcellulose Akucell AF 2085 (sodium content 8%), and medium-viscosity hydroxypropylcellulose Klucel GF in water, wherein the concentration of Akucell AF 1505 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 parts by weight), and the concentration of Akucell AF 2085 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 parts by weight). The concentration of 2085 is 3% wt / wt (based on the final total amount of 100%, that is, it contains 3 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 3% wt / wt (based on the final total amount of 100%, that is, it contains 3 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.4 times the (molar) amount of total sodium in the above sodium carboxymethyl cellulose, the mixture is mixed, and small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200Da to obtain a colloidal solution A;
[0049] 2) Add a water-dispersed solution of the prototype lidocaine nanopowder to the colloidal solution A, wherein the molar amount of lidocaine is 0.98-1 times the molar amount of the above hydrochloric acid, and add lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.2 times the molar amount of the above hydrochloric acid, mix well, and place at room temperature for 2-4 hours to obtain a colloidal solution B;
[0050] 3) Sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons is added to colloidal solution B at a concentration of 4% wt / wt (based on the final total amount of 100%, i.e., 4 parts per 100 parts by weight), to obtain colloidal solution C;
[0051] 4) Add 8% wt / wt (based on the final total amount of 100%, that is, 8 parts per 100 parts by weight) of polymethyl methacrylate microspheres and 12% wt / wt (based on the final total amount of 100%, that is, 12 parts per 100 parts by weight) of glycerol to the colloidal solution C, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).
[0052] Comparative Example 2-1
[0053] 90% (i.e., 10% of the original amount) of Akucell AF 1505 (viscosity of 40-70 mPa·s at a concentration of 1% wt / wt) in Example 2 was replaced with Akucell AF 2085 (viscosity of 200-400 mPa·s at a concentration of 1% wt / wt), and the rest remained unchanged.
[0054] Comparative Example 2-2
[0055] 90% of the amount of Akucell AF 2085 in Example 2 (ie, 10% of the original amount) was replaced with Akucell AF 1505, and the rest remained unchanged.
[0056] Example 3
[0057] 1) Disperse low-viscosity sodium carboxymethylcellulose Akucell AF 1505 (sodium content 8%), medium-viscosity sodium carboxymethylcellulose Akucell AF 2085 (sodium content 8%), and medium-viscosity hydroxypropylcellulose Klucel GF in water, wherein the concentration of Akucell AF 1505 is 4% wt / wt (based on the final total amount of 100%, that is, 4 parts per 100 parts by weight), and the concentration of Akucell AF 2085 is 4% wt / wt (based on the final total amount of 100%, that is, 4 parts per 100 parts by weight). The concentration of 2085 is 2% wt / wt (based on the final total amount of 100%, that is, it contains 2 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 4% wt / wt (based on the final total amount of 100%, that is, it contains 4 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.3 times the (molar) amount of total sodium in the above sodium carboxymethyl cellulose, the mixture is mixed, and small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200 Da to obtain a colloidal solution A;
[0058] 2) Add a water-dispersed solution of the prototype lidocaine nanopowder to the colloidal solution A, wherein the molar amount of lidocaine is 0.98-1 times the molar amount of the above hydrochloric acid, and add lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.25 times the molar amount of the above hydrochloric acid, mix well, and place at room temperature for 2-4 hours to obtain a colloidal solution B;
[0059] 3) Sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons is added to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight), to obtain colloidal solution C;
[0060] 4) Add 6% wt / wt (based on the final total amount of 100%, that is, 6 parts per 100 parts by weight) of polymethyl methacrylate microspheres and 10% wt / wt (based on the final total amount of 100%, that is, 10 parts per 100 parts by weight) of glycerol to the colloidal solution C, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).
[0061] Comparative Example 3-1
[0062] The sodium hyaluronate with a molecular weight of 800,000-1.2 million daltons and a concentration of 3% wt / wt in Example 3 was replaced with sodium hyaluronate with a molecular weight of 800,000-1.2 million daltons and a concentration of 0.3% wt / wt, and the rest remained unchanged.
[0063] Comparative Example 3-2
[0064] The sodium hyaluronate with a molecular weight of 800,000-1.2 million daltons and a concentration of 3% wt / wt in Example 3 was replaced with sodium hyaluronate with a molecular weight of 800,000-1.2 million daltons and a concentration of 9% wt / wt, and the rest remained unchanged.
[0065] Example 4
[0066] 1) Disperse low-viscosity sodium carboxymethylcellulose Akucell AF 1505 (sodium content 8%), medium-viscosity sodium carboxymethylcellulose Akucell AF 2085 (sodium content 8%), and medium-viscosity hydroxypropylcellulose Klucel JF in water, wherein the concentration of Akucell AF 1505 is 5% wt / wt (based on the final total amount of 100%, that is, 5 parts per 100 parts by weight), and the concentration of Akucell AF 2085 is 5% wt / wt (based on the final total amount of 100%, that is, 5 parts per 100 parts by weight). The concentration of 2085 is 2% wt / wt (based on the final total amount of 100%, that is, it contains 2 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 5% wt / wt (based on the final total amount of 100%, that is, it contains 5 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.35 times the (molar) amount of total sodium in the above sodium carboxymethyl cellulose, the mixture is mixed, and small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200Da to obtain a colloidal solution A;
[0067] 2) Add a water-dispersed solution of prototype lidocaine nanopowder to colloidal solution A, wherein the molar amount of lidocaine is 0.98-1 times the molar amount of the above hydrochloric acid, and add lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.25 times the molar amount of the above hydrochloric acid, mix well, and place at room temperature for 2-4 hours to obtain colloidal solution B;
[0068] 3) Sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons is added to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight), to obtain colloidal solution C;
[0069] 4) Add 5% wt / wt (based on the final total amount of 100%, that is, 5 parts per 100 parts by weight) of polymethyl methacrylate microspheres and 6% wt / wt (based on the final total amount of 100%, that is, 6 parts per 100 parts by weight) of glycerol to the colloidal solution C, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).
[0070] Comparative Example 4-1
[0071] The molar amount of hydrochloric acid in Example 4 is 0.35 times the molar amount of the total sodium in the above-mentioned sodium carboxymethyl cellulose, and is replaced by the molar amount of hydrochloric acid being 0.02 times the molar amount of the total sodium in the above-mentioned sodium carboxymethyl cellulose, and
[0072] The molar amount of the added prototype lidocaine and the molar amount of the added lidocaine hydrochloride were the same as those in Example 4.
[0073] Everything else remains unchanged.
[0074] Comparative Example 4-2
[0075] The molar amount of hydrochloric acid in Example 4 is 0.35 times the molar amount of the total sodium in the above-mentioned sodium carboxymethyl cellulose, and is replaced by the molar amount of hydrochloric acid being 0.98 times the molar amount of the total sodium in the above-mentioned sodium carboxymethyl cellulose, and
[0076] The molar amount of the added prototype lidocaine and the molar amount of the added lidocaine hydrochloride were the same as those in Example 4.
[0077] Everything else remains unchanged.
[0078] Example 5
[0079] 1) Disperse low-viscosity sodium carboxymethylcellulose Akucell AF 1505 (sodium content 8%), medium-viscosity sodium carboxymethylcellulose Akucell AF 2085 (sodium content 8%), and medium-viscosity hydroxypropylcellulose Klucel GF in water, wherein the concentration of Akucell AF 1505 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 parts by weight), and the concentration of Akucell AF 2085 is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 parts by weight). The concentration of 2085 is 3% wt / wt (based on the final total amount of 100%, that is, it contains 3 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 3% wt / wt (based on the final total amount of 100%, that is, it contains 3 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the (molar) amount of hydrochloric acid is 0.4 times the (molar) amount of total sodium in the above sodium carboxymethyl cellulose, the mixture is mixed, and small molecules are removed by filtering with a nanofiltration membrane with a pore size of 200Da to obtain a colloidal solution A;
[0080] 2) Add a water-dispersed solution of the prototype lidocaine nanopowder to the colloidal solution A, wherein the molar amount of lidocaine is 0.98-1 times the molar amount of the above hydrochloric acid, and add lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.2 times the molar amount of the above hydrochloric acid, mix well, and place at room temperature for 2-4 hours to obtain a colloidal solution B;
[0081] 3) Sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons is added to colloidal solution B at a concentration of 4% wt / wt (based on the final total amount of 100%, i.e., 4 parts per 100 parts by weight), to obtain colloidal solution C;
[0082] 4) Add 8% wt / wt (based on the final total amount of 100%, that is, 8 parts per 100 parts by weight) of polymethyl methacrylate microspheres and 12% wt / wt (based on the final total amount of 100%, that is, 12 parts per 100 parts by weight) of glycerol to the colloidal solution C, add water to the total amount (100%), mix well, and obtain (or further put into a container so that the liquid layer thickness is 0.1-2 mm, freeze-dry, and remove the solvent).
[0083] Comparative Example 5-1
[0084] The concentration of hydroxypropyl cellulose in Example 5 was changed from 3% wt / wt to 0.3% wt / wt, and the other contents remained unchanged.
[0085] Comparative Example 5-2
[0086] The concentration of hydroxypropyl cellulose in Example 5 was changed from 3% wt / wt to 9% wt / wt, and the other contents remained unchanged.
[0087] Test Example 1
[0088] The samples of the embodiment and the control example were diluted with physiological saline (added with 0.05% calcium ion) at a ratio of 1:1 and placed at room temperature for 0, 1, 2, 4 and 6 months, and the turbidity values (NTU) were measured using a Hach turbidimeter.
[0089] The results are shown in Table 1.
[0090] Table 1-1 Turbidity values (NTU) measured in Example 1 and its comparative example
[0091] 0 month January February April June Example 1 2.7 2.9 3.2 3.7 4.5 Comparative Examples 1-5 4.5 6.7 10.3 18.5 27.5 Comparative Examples 1-6 -★ - - - -
[0092] ★Explanation: No qualified samples were obtained, and the turbidity was not tested. The viscosity of the hydroxypropylcellulose Klucel MF in control examples 1-6 was too high, resulting in a sample similar to jelly.
[0093] Table 1-2 Turbidity values (NTU) measured in Example 3 and its comparative example
[0094] 0 month January February April June Example 3 2.2 2.6 3.1 4.0 5.2 Comparative Example 3-1 6.1 9.3 13.2 22.8 32.3 Comparative Example 3-2 -★ - - - -
[0095] ★Description: No qualified samples were obtained, and the turbidity was not tested. The control example 3-2 formed a sample similar to jelly because the molecular weight of sodium hyaluronate was 800,000-1.2 million Daltons.
[0096] Table 1-3 Turbidity values (NTU) measured in Example 4 and its comparative example
[0097] 0 month January February April June Example 4 2.2 2.6 3.1 4.0 5.2 Comparative Example 4-1 12.1 18.3 31.2 40.8 65.3 Comparative Example 4-2 8.3 12.6 16.8 26.7 38.7
[0098] Table 1-4 Turbidity values (NTU) measured in Example 5 and its comparative example
[0099] 0 month January February April June Example 5 2.5 2.8 3.5 4.3 5.6 Comparative Example 5-1 4.3 6.9 9.9 17.6 25.7 Comparative Example 5-2 -★ - - - -
[0100] ★Explanation: No qualified samples were obtained, and the turbidity was not tested. The viscosity of the control example 5-2, hydroxypropylcellulose Klucel GF, was too high, resulting in a sample similar to jelly.
[0101] The results show that the embodiments have lower turbidity values, better dispersion, smaller particles, better storage stability, and higher salt resistance than the control examples.
[0102] Test Example 2
[0103] The samples of the embodiment and the control example were diluted with purified water and physiological saline at a ratio of 1:1 to prepare pre-filled needles, which were sterilized by γ-ray irradiation.
[0104] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests and intradermal injection experiments have demonstrated that the prefilled needle is non-toxic, has no hemolytic effect, is non-irritating, does not contain pyrogenic substances, has stable performance and good biocompatibility.
[0105] 2 mL of the above prefilled needle was subcutaneously injected on both sides of the face of 468 patients with moderate to severe nasolabial wrinkles, and the analgesic effects of the prefilled needles of the embodiment and the control example were compared and observed.
[0106] The visual analogue scale (VAS) of pain in the embodiment and control groups was calculated at 6h, 12h, 24h, 36h, 48h and 72h after surgery in the resting state and the active state. The score of no pain was 0, the score of disturbing sleep was 5, the score of severe pain was 10, and the higher the score, the more severe the pain.
[0107] The occurrence of adverse reactions to postoperative analgesia in patients in the embodiment and control groups was counted separately, including symptoms such as nausea, dizziness, palpitations, sweating, etc., and the adverse reaction rate = number of adverse reaction cases / total number of cases × 100%.
[0108] The VAS score results of the subjects after receiving the sample treatment are shown in Table 2.
[0109] The adverse reaction rates of the subjects after receiving the sample treatment are shown in Table 3.
[0110] Table 2-1 VAS score results after the subjects received sample treatment
[0111] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 1 1.53±0.31 2.84±0.52 3.04±0.37 3.24±0.38 3.38±0.45 3.47±0.48 Comparative Example 1-1 1.46±0.33 2.76±0.54 3.21±0.42 3.67±0.43 5.88±0.57 6.64±0.53 Comparative Example 1-2 1.92±0.36 3.46±0.47 4.12±0.46 4.32±0.42 4.74±0.63 5.13±0.75 Comparative Examples 1-3 2.07±0.38 3.86±0.43 4.11±0.42 4.32±0.56 4.63±0.48 5.04±0.47 Comparative Examples 1-4 1.41±0.37 2.70±0.48 3.57±0.54 4.55±0.46 6.09±0.72 6.89±0.73
[0112] Table 2-2 Results of VAS scores after subjects received sample treatment
[0113] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 2 1.26±0.33 1.84±0.31 2.55±0.35 2.76±0.39 2.98±0.43 3.07±0.47 Comparative Example 2-1 1.23±0.34 1.62±0.37 2.77±0.44 3.52±0.46 5.42±0.52 6.24±0.58 Comparative Example 2-2 1.86±0.34 3.71±0.56 4.02±0.52 4.11±0.54 4.27±0.55 4.47±0.52
[0114] Table 2-3 VAS score results after the subjects received sample treatment
[0115] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 3 1.20±0.31 1.56±0.33 2.07±0.38 2.42±0.39 2.82±0.43 3.01±0.48 Comparative Example 3-1 1.03±0.23 1.38±0.28 2.11±036 3.04±0.42 4.23±0.51 5.13±0.62 Comparative Example 3-2 -★ - - - - -
[0116] ★Note: No qualified samples were obtained and the experiment was not carried out.
[0117] Table 2-4 VAS score results after the subjects received sample treatment
[0118] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 4 1.33±0.32 1.64±0.34 2.12±0.37 2.47±0.39 2.88±0.46 3.07±0.52 Comparative Example 4-1 1.22±0.24 1.51±0.36 2.87±0.34 4.36±0.48 6.02±0.67 6.73±0.77 Comparative Example 4-2 1.73±0.37 3.32±0.41 3.88±0.48 4.06±0.52 4.23±0.51 4.32±0.57
[0119] Table 2-5 VAS score results after the subjects received sample treatment
[0120] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 5 1.23±0.30 1.52±0.32 2.03±0.36 2.45±0.37 2.78±0.40 2.97±0.46 Comparative Example 5-1 1.07±0.21 1.35±0.27 2.16±032 3.08±0.45 4.27±0.54 5.22±0.65 Comparative Example 5-2 -★ - - - - -
[0121] ★Note: No qualified samples were obtained and the experiment was not carried out.
[0122] Table 3-1 Adverse reaction rate results after subjects received sample treatment
[0123] Adverse reaction rate% Example 1 24 Comparative Example 1-1 42 Comparative Example 1-2 22 Comparative Examples 1-3 20 Comparative Examples 1-4 51
[0124] Table 3-2 Adverse reaction rate results after subjects received sample treatment
[0125] Adverse reaction rate% Example 2 26 Comparative Example 2-1 47 Comparative Example 2-2 24
[0126] Table 3-3 Adverse reaction rate results after subjects received sample treatment
[0127]
[0128]
[0129] Table 3-4 Adverse reaction rate results after subjects received sample treatment
[0130] Adverse reaction rate% Example 4 25 Comparative Example 4-1 60 Comparative Example 4-2 21
[0131] Table 3-5 Adverse reaction rate results after subjects received sample treatment
[0132] Adverse reaction rate% Example 5 23 Comparative Example 5-1 45
[0133] The results show that the embodiments have better drug release performance and better analgesic effect than the control examples, or have equivalent analgesic effect but lower incidence of side effects.
[0134] The analgesic effect of the embodiment is as long as several days, which meets clinical needs and is consistent with actual needs, and is neither too long nor too short. The drug effect of ordinary gel sustained-release preparations lasts only a few hours to more than ten hours, while the drug is dispersed in polyester sustained-release preparations such as PCL, and the drug effect lasts for several weeks to several months, which is obviously too long or too short for analgesia.
[0135] When the control example releases the drug faster, the initial analgesic effect is slightly better than that of the embodiment, but the effect becomes worse in the later stage, and the incidence of side effects is relatively higher.
[0136] When the drug release rate of the control example was low, the analgesic effect was always poorer than that of the embodiment, and the incidence of side effects was slightly lower.
Claims
1. A method for preparing a lidocaine long-term sustained-release prefilled needle, the method comprising: 1) Disperse low-viscosity sodium carboxymethyl cellulose, medium-viscosity sodium carboxymethyl cellulose and medium-viscosity hydroxypropyl cellulose in water, wherein the concentration of low-viscosity sodium carboxymethyl cellulose is 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight are contained in the final solution, the concentration of medium-viscosity sodium carboxymethyl cellulose is 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight are contained in the final solution, and the concentration of hydroxypropyl cellulose is 2-6% wt / wt, i.e., 2-6 parts per 100 parts by weight are contained in the final solution, and hydrochloric acid solution is added to convert sodium carboxymethyl cellulose into acid sodium carboxymethyl cellulose, wherein the molar amount of hydrochloric acid is 0.1-0.5 times the molar amount of total sodium in the sodium carboxymethyl cellulose, and mix well to obtain colloidal solution A. , the above-mentioned sodium carboxymethyl cellulose has a degree of substitution of 0.7-1, a sodium content of about 8% wt / wt, a degree of neutralization of 95-100%, and a viscosity of 40-70mpa·s at a concentration of 1% wt / wt; the above-mentioned sodium carboxymethyl cellulose with a medium viscosity has a degree of substitution of 0.7-1, a sodium content of about 8% wt / wt, a degree of neutralization of 95-100%, and a viscosity of 200-400mpa·s at a concentration of 1% wt / wt; the above-mentioned hydroxypropyl cellulose with a medium viscosity has a molecular weight of 140,000 Daltons, a viscosity of 150-400mpa·s at a concentration of 5% wt / wt, or / and a molecular weight of about 370,000 Daltons, and a viscosity of 150-400mpa·s at a concentration of 2% wt / wt; 2) Adding prototype lidocaine or its ethanol solution or its aqueous dispersion to colloidal solution A, wherein the molar amount of lidocaine is 0.95-1 times the molar amount of hydrochloric acid in the above hydrochloric acid solution, and adding lidocaine hydrochloride, wherein the molar amount of lidocaine hydrochloride is 0.2-0.5 times the molar amount of hydrochloric acid in the above hydrochloric acid solution, mixing, and leaving at room temperature for 2-4 hours to obtain colloidal solution B; 3) Adding sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight, to obtain colloidal solution C; 4) Add polycaprolactone microspheres and / or polymethyl methacrylate microspheres and / or polylactic acid copolymer and / or glycerol to the colloidal solution C, add water to the total amount, mix well, and obtain the product.
2. The preparation method according to claim 1, characterized in that The concentration of the low-viscosity sodium carboxymethyl cellulose is 3-4% wt / wt.
3. The preparation method according to claim 1, characterized in that The concentration of the medium viscosity sodium carboxymethyl cellulose is 2-3% wt / wt.
4. The preparation method according to claim 1, characterized in that The concentration of the hydroxypropyl cellulose is 3-4% wt / wt.
5. The preparation method according to claim 1, characterized in that The dosage ratio of the low-viscosity sodium carboxymethyl cellulose to the medium-viscosity sodium carboxymethyl cellulose is 1:0.5-1.
5.
6. The preparation method according to claim 1, characterized in that The dosage ratio of the low-viscosity sodium carboxymethyl cellulose to the medium-viscosity sodium carboxymethyl cellulose is 1:0.8-1.2.
